The multi-dimensional talent support tool (mBET) - Stahl, Johanna (Psihološka obzorja (Ljubljana), 2014)
Providing gifted students with personalized talent development programs is a challenge for teachers and educators alike. The multi-dimensional talent development tool (mBET) guides teachers on their way to individualized gifted programs. Within a holistic and systemic concept of giftedness, the mBET brings together the perspectives of teachers, parents and the individual student in assessing talents as well as relevant personality characteristics and environment factors. By facilitating support-oriented round-table talks, the mBET helps teachers, parents and students to develop individually tailored talent development programs, taking into consideration both talents and other factors relevant for successful gifted education (i.e. non-cognitive personality characteristics and environmental factors).
Keywords: education; vzgoja in izobraževanje; gifted; nadarjeni; Austria; Avstrija